ANALISIS GERAKAN POLITIK ALIANSI MASYARAKAT SIPIL DALAM PENOLAKAN EKSPLOITASI TAMBANG MANGAN DI KAMPUNG TUMBAK KABUPATEN MANGGARAI TIMUR - Firman Gili, Yohanes; Noak, Piers Andreas; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2018)
ABSTRAC T This research aims to determine a things behind the resistance af the Community Alliance according to the decree by the Head of East Manggarai Regancy number HK.81-2009 in Lambaleda Distrik and same factors that influence the resistance Alliance Movement’s can be success. The informants in this study are eight people who are member of the Movment Alliance are pastors, youth leaders (student), local goverments Alliance and parties involvet in Alliance Society resistance. This research was conduted in Lambaleda Districk, East Manggarai Regency, East Nusa Tenggara Timur province, the research time was from june 2016 until august 2016. Research metho with direct interview and documentation. Data analisis used descriptive qualitative to describe and explain a background of Community Alliance make a resistance movement of mine in East Manggarai Regency succeed. The result of this study have explained, there are several factors behind the resistance movement by Community Alliance which are the lack of community involvement in the formulation of the policy, the lack of the socialization conducted by the Government and the police that’s not target. Some of these factors caused the emergency of the resistance movement by the Community Alliance of hiden resistance (not organized) and open resistance (organized) Keywords : Community Alliance, Resistance, Mining Business License (MBL)